1)x^2+9x+8 (x+1)(x+8) (x+8)
==
3x^2+8x+5 3(x+1)(x+1 2/3) 3x+5
x^2+9x+8=0 3x^2+8x+5=0
D= 8^2-4*3*5=64-60=4
x1+x2=-9| -8(+)-))2
x1,2=
|-8;-1 6
x1x2=8 | x1=-1 ; x2=-1 2/3
2)
a)x(x+3)-4(x-5)=7(x+4)-8
x^2+3x-4x+20=7x+28-8
x^2-8x=0
x(x-8)=0
x=0 или х-8=0
х=8
б)2x^4-9x+4=0
D=(-9)^2-4*2*4=81-32=49
9(+(-))7
x1,2=
4
x1=4; x2=0.5
В решении.
Объяснение:
Найдите значение выражений:
1) (3-x)²-x(x-21) = при x= -2,84
= 9 - 6х + х² - х² +21х =
= 9 + 15х =
=9 + 15 * (-2,84) =
=9 - 42,6 = -33,6.
2) d⁷×(d³)⁻¹ = при d= -2
= d⁷ * 1/d³ =
= d⁷/d³ = d⁷⁻³ = d⁴ = (-2)⁴ = 16.
3) a + (2y-a²)/a = при a= -10 и y=19
общий знаменатель а:
= (а*а + 2у - а²)/а =
= (а² + 2у - а²)/а =
=2у/а = 2*19/(-10) = 38/(-10) = -3,8.